Achieving Service-Learning Goals in a Financial Accounting Class Project - Yu, Darwin D (Archīum Ateneo, 2011)
Background: A financial accounting class in a Philippine university has a service-learning group project that involves setting up a simple accounting system for microenterprises. Aims: This paper examines the extent to which service-learning goals such as course learning, teamwork, civic responsibility, and impact on the client organization are achieved through this project, as well as how the level of student participation affects the achievement of these service-learning goals. It identifies measures to improve the quality of the service-learning experience for future implementation. Sample: 187 second year business students in a Philippine university Method: The students filled out a questionnaire which asked about their level of participation in the project, and their sense of achieving certain cognitive and affective outcomes from the project. Results: Results show that these goals have been achieved to a large extent through the project, and that the level of student participation does positively affect the level of achievement of these goals. Furthermore, the achievement levels among the service-learning goals are significantly correlated, such that they seem to be mutually-reinforcing. Conclusion: This paper supports the growing body of research work about the multiple benefits that service-learning brings to students, communities, and future citizenship in business fields of study. The accounting service-learning experience can be improved through better identification and screening of participating microenterprises, and through better management of student expectations regarding the magnitude of data-gathering needed for the project.